2021
DOI: 10.1097/md.0000000000024747
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic lumbar discectomy compared with other surgeries for lumbar disc herniation

Abstract: Objective: This meta-analysis was performed to investigate whether percutaneous endoscopic lumbar discectomy (PELD) had a superior effect than other surgeries in the treatment of patients with lumbar disc herniation (LDH). Method: We searched PubMed, Embase, and Web of Science through February 2018 to identify eligible studies that compared the effects and complications between PELD and other surgical interventions in LDH. The outcomes included success rate, recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The advantages of this method include no bone removal, reduction of complications, minor wounds, reduction of bleeding, reduction of fluid requirements, no need for catheterization, reduction of hospitalization period, very low complication rate, rapid recovery, return to work, and reduction of costs. The safety and effectiveness of this treatment have been confirmed by several randomized studies (18)(19)(20). On the other hand, because this procedure is performed under LA or EA, the patient is conscious during surgery, and damage to the spinal cord is prevented (13,21).…”
Section: Discussionmentioning
confidence: 78%
“…The advantages of this method include no bone removal, reduction of complications, minor wounds, reduction of bleeding, reduction of fluid requirements, no need for catheterization, reduction of hospitalization period, very low complication rate, rapid recovery, return to work, and reduction of costs. The safety and effectiveness of this treatment have been confirmed by several randomized studies (18)(19)(20). On the other hand, because this procedure is performed under LA or EA, the patient is conscious during surgery, and damage to the spinal cord is prevented (13,21).…”
Section: Discussionmentioning
confidence: 78%
“…Low back pain is accepted as a derivative of multi-origin somatic pain with its physical, psychogenic and social aspects, and the problem of DIVD emerges as the most important source of this pain in the lumbar spine (11,12). An inflammatory condition in DIVD is a kind of antiinjury response to injury in the skeleton, and it plays a crucial efficiency in the development and worsening of DIVD (13).…”
Section: Discussionmentioning
confidence: 99%
“…The scenarios for each paper were drawn from §3.0.2. For each scenario, we selected a single paper ( [98] for SLE and [8] for a herniated disc) for participants to read based on the most common papers readers selected in §3.…”
Section: Usability Studymentioning
confidence: 99%
“…We adapted our GPT-3 prompt and generation parameters (e.g., length of generation and temperature) from one of the preset examples that OpenAI provides for summarizing text for a 2nd grader. 8 We changed the prompt to summarize for a 5th grader rather than 2nd grader after observing that using 2nd grader caused the model output to be too general and vague. We also tested later grades, up to college, but found that the generated text using the 5th grader prompt was the most consistent.…”
Section: Paper Plain Implementation C1 Gpt-3 Simplificationmentioning
confidence: 99%